Framework for Integrating Passive Design Strategies in Sustainable Green Residential Construction - Sidney Eronmonsele Okiye; Tochi Chimaobi Ohakawa; Zamathula Sikhakhane Nwokediegwu (International Journal of Scientific Research in Civil Engineering, 2023)
Sustainable green residential construction has emerged as a crucial aspect of modern architectural and engineering practices, primarily driven by the urgent need to mitigate environmental degradation and reduce carbon footprints in housing developments. Among the strategies employed to achieve sustainability, passive design methods have gained significant attention due to their ability to enhance energy efficiency without relying heavily on mechanical systems. This paper explores a structured framework for integrating passive design strategies into sustainable green residential construction, focusing on techniques that optimize natural lighting, ventilation, and thermal regulation to create eco-friendly living spaces. Passive design principles leverage site orientation, building envelope design, material selection, and vegetation integration to minimize energy consumption while maximizing indoor comfort. By systematically incorporating these elements, residential structures can achieve enhanced functionality, reduced operational costs, and improved overall sustainability. Additionally, this framework considers the social, economic, and regulatory aspects influencing the adoption of passive design strategies, addressing key challenges such as financial constraints, policy limitations, and awareness gaps among stakeholders. The study synthesizes existing methodologies and presents a cohesive model that aligns with contemporary architectural practices, promoting a holistic approach to green residential development. By examining relevant case studies, the research highlights best practices and potential areas for improvement in passive design implementation. The findings aim to serve as a guiding framework for architects, engineers, and policymakers seeking to advance the principles of sustainable housing through passive design innovation.
Keywords: Passive design; sustainable construction; green residential housing; energy efficiency; building envelope; thermal regulation; ventilation strategies